Recurrent spontaneous abortion related to balanced translocation of chromosomes – A case report - N. Dukuze; B. Tuyishimire; H. Irere; B. Iradukunda; J. Ndinkabandi; C. Nsanzabaganwa; J. Mushingantahe; L. Mutesa (Rwanda Medical Journal, 2023)
INTRODUCTION: Recurrent spontaneous abortion (RSA) is defined as three or more consecutive pregnancy losses before the 20th week of gestation. RSA is often idiopathic, but structural chromosomal abnormality is an important cause. An unbalanced karyotype in the conceptus of a couple when one partner has a structural chromosomal abnormality may result in failure to implant, miscarriage, or pregnancy of a fetus with an unbalanced karyotype. CASE PRESENTATION: We report a rare case of RSA associated with balanced translocation of chromosomes. a woman who had four spontaneous abortions, all pregnancy loss happened before 12 weeks of gestation, no other known chronic diseases reported to the family nor medications taken during pregnancy. The karyotype was 46.XX, t(13p,21p) The abnormal karyotype was not found in any other chromosomes. Further spectral karyotyping was performed to rule out the involvement of any other chromosomal aberrations present in the genome.The cytogenetic analysis of the husband revealed a normal karyotype 46.XY. CONCLUSION: Couples with more than three miscarriages should be referred to the genetist for chromosomal analysis for possible hereditary etiology and chromosomal abnormalities responsible for miscarriages to plan prenatal diagnostics and genetic counseling for subsequent pregnancies.